1985
DOI: 10.1021/bi00344a048
|View full text |Cite
|
Sign up to set email alerts
|

Essential light chain exchange in scallop myosin

Abstract: The exchange of essential light chains (SH-LCs) of scallop myosin was followed with the aid of scallop SH-LC alkylated with 14C-labeled iodoacetate. More than 70% of the SH-LCs were exchanged in myosin preparations that were desensitized by removal of both regulatory light chains (R-LCs) with ethylenediaminetetraacetic acid (EDTA) treatment. Although desensitized myosin solubilized with 0.6 M NaCl or with 10 mM adenosine 5'-triphosphate (ATP) in the absence of salt equilibrated rapidly with SH-LCs even in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…When scallop R-LC was removed totally by EDTA treatment prior to TFP addition, E-LC removal remained refractory to TFP treatment, although some small losses (Ͻ5%) did occur (data not shown). Such losses are consistent with data suggesting that prior R-LC removal destabilizes E-LC attachment to the myosin heavy chain (21,29). For smooth muscle myosin, a combined treatment of 5-10 mM TFP and 4.5 M ammonium chloride facilitates E-LC exchange and even complete removal of both R-LCs and E-LCs (21,30).…”
Section: Discussionsupporting
confidence: 88%
“…When scallop R-LC was removed totally by EDTA treatment prior to TFP addition, E-LC removal remained refractory to TFP treatment, although some small losses (Ͻ5%) did occur (data not shown). Such losses are consistent with data suggesting that prior R-LC removal destabilizes E-LC attachment to the myosin heavy chain (21,29). For smooth muscle myosin, a combined treatment of 5-10 mM TFP and 4.5 M ammonium chloride facilitates E-LC exchange and even complete removal of both R-LCs and E-LCs (21,30).…”
Section: Discussionsupporting
confidence: 88%
“…However, Okamoto et al (1986) have shown that MLC1 binds near the site of ATP binding on smooth muscle myosin. In the scallop it has been shown that exchange of MLC1 with exogenously added MLC1 can occur only in the absence of MLC2 (Ashiba and Szent-Gyorgyi, 1985). This finding, coupled with the observation that the 1.…”
mentioning
confidence: 95%
“…2B), indicating that oxygen-containing side A 1 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) I (57-68) Hybrid RDs containing the cardiac ELC, the CI-SCII,SCIII,SCIV chimera, and the C1,CII-SCIII,SCIv chimera were formed and were isolated as stable complexes by ion-exchange chromatography ( Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%